2009
DOI: 10.1002/hec.1535
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of opportunity in health: evidence from a UK cohort study

Abstract: SUMMARYThis paper proposes an empirical implementation of the concept of inequality of opportunity in health and applies this to data from the UK National Child Development Study. Drawing on the distinction between circumstance and effort variables in John Roemer's work on equality of opportunity, circumstances are proxied by parental socioeconomic status and childhood health; effort is proxied by health-related lifestyles and educational attainment. Stochastic dominance tests are used to detect inequality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 38 publications
1
59
0
3
Order By: Relevance
“…It is thus an important question for the understanding of social health inequalities to know the share of the latter that may be attributable to the direct effect of social background and to the transmission of health status across generations, due to the unequal distribution of family background across wealth groups. Pioneered by Bourdieu [18], the theory of social reproduction across generations has been well-studied and confirmed in numerous empirical research studies in economics and sociology [17,[19][20][21]. More recently, the PISA follow-up survey focussing on education achievement and social background of young Europeans aged between 16 and 35 has shown that there is a substantial reproduction effect by the transmission of cultural capital in the family.…”
Section: Introductionmentioning
confidence: 98%
“…It is thus an important question for the understanding of social health inequalities to know the share of the latter that may be attributable to the direct effect of social background and to the transmission of health status across generations, due to the unequal distribution of family background across wealth groups. Pioneered by Bourdieu [18], the theory of social reproduction across generations has been well-studied and confirmed in numerous empirical research studies in economics and sociology [17,[19][20][21]. More recently, the PISA follow-up survey focussing on education achievement and social background of young Europeans aged between 16 and 35 has shown that there is a substantial reproduction effect by the transmission of cultural capital in the family.…”
Section: Introductionmentioning
confidence: 98%
“…We note that lower percentage in these studies are always associated with one (or two) circumstances, thus, causality issue on partial circumstances matters and it confirms the idea that the share of inequality of opportunity can only be defined as a lower bound estimate of the ‘true’ inequality of opportunity. The Gini opportunity index advanced by Le Franc et al (2008) capture on average around 15% of income inequality of opportunity for nine developed countries while in the health context it counts for 21–26% in UK as verified by Rosa Dias (2009). According to health analysis, striking results are obtained by Jusot et al (2010) who observe around 45% of inequality of opportunity in France using CV and variance.…”
Section: Measuring Inequality Of Opportunitymentioning
confidence: 90%
“… See Fleurbaey and Shokkaert (2009), Rosa Dias (2009), Trannoy et al (2009) for an overview about the measurement of inequality of opportunity in health. …”
mentioning
confidence: 99%
“…Inspired by the philosophical concept of equality of opportunity developed by Dworkin (1981a,b), Roemer (1998), andFleurbaey (2008), a number of recent publications in health economics have focused on drawing the line between legitimate and illegitimate 3 causes of health inequalities (Fleurbaey and Schokkaert 2009;Dias 2009;Trannoy et al 2010;Dias 2010;Jusot et al 2013). The 1 For a review of policies aiming at changing health-related behaviours, see for example Cawley (2011).…”
Section: Three Constraints For Individual Choicesmentioning
confidence: 99%